2020
DOI: 10.2499/p15738coll2.133653
|View full text |Cite
|
Sign up to set email alerts
|

Gender dynamics, women’s empowerment, and diets: Qualitative findings from an impact evaluation of a nutrition-sensitive poultry value chain intervention in Burkina Faso

Abstract: in 1975, provides research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. IFPRI's strategic research aims to foster a climate-resilient and sustainable food supply; promote healthy diets and nutrition for all; build inclusive and efficient markets, trade systems, and food industries; transform agricultural and rural economies; and strengthen institutions and governance. Gender is integrated in all the Institute's work. Partnerships, communications, capacity strengthening,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…These results may suggest a change toward more equitable or shared parenting, where more empowered women have more engaged partners. Indeed, in West Africa, empowered women are those who manage the family in tandem with their partners [61]. In South Africa, more empowered women who enter the workforce have more engaged partners who spend more time with their children [62].…”
Section: Plos Medicinementioning
confidence: 99%
“…These results may suggest a change toward more equitable or shared parenting, where more empowered women have more engaged partners. Indeed, in West Africa, empowered women are those who manage the family in tandem with their partners [61]. In South Africa, more empowered women who enter the workforce have more engaged partners who spend more time with their children [62].…”
Section: Plos Medicinementioning
confidence: 99%
“…They therefore did not provide any examples where they (the man) or their wives would voice anything related to how the other utilized his or her time. Men from Niger state are more likely to be polygynous, which may explain some of these differences between participants from Niger and Anambra states, as polygynous men are less likely than monogamous men to discuss matters with their wives, or perhaps only with the first wife (see Eissler et al., 2020 for a discussion of these dynamics in Burkina Faso).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Burkina Faso, focus groups showed that men are considered the head decision-makers around poultry production and marketing. But beneficiary women in a poultry value chain intervention said raising poultry increased their self-confidence in their skills and capacities; gaining financial independence was critical, as they no longer needed to rely on their husbands' permission or direction on how to spend money (Eissler et al 2020). In Malawi, many women are tied by the norms dictating the role of a "good wife" who often must defer to her husband.…”
Section: Figure 93-distribution Of Project Impacts On Women's and Men...mentioning
confidence: 99%